Tingkat Kecemasan Atlet Judo Kota Salatiga Sebelum Menghadapi Pertandingan (Universitas Negeri Semarang, 2022)
The background of the problem in this study is, all Judo athletes in Salatiga City have faced a match. Many athletes experience anxiety before facing a match. The formulation of the problem in this research is how much anxiety level of Judo athletes in Salatiga City before facing a match? The purpose of this study was to find out how much anxiety level of Judo athletes in Salatiga City was before facing a match. This study uses a quantitative method with a correlation design and sampling with a total sampling technique. Data collection using questionnaires and data analysis techniques using descriptive statistics. The results showed that the level of concern was 73,5%, wich was inthe high category. The level of concentration disturbance was 60,2%, which is in the moderate category. And the level of somatic anxiety was 68,9%, is in the high category. Data obtained from athlete’s anxiety levels, 8 athletes (40%) were at the moderte level and 12 athletes (60%) were at the high level. The average anxiet level of Judo athletes in Salatiga City is 49,2, in the high category.